2021
DOI: 10.1126/sciadv.abe7871
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a natural cyan blue: A unique food-sourced anthocyanin could replace synthetic brilliant blue

Abstract: The color of food is critical to the food and beverage industries, as it influences many properties beyond eye-pleasing visuals including flavor, safety, and nutritional value. Blue is one of the rarest colors in nature’s food palette—especially a cyan blue—giving scientists few sources for natural blue food colorants. Finding a natural cyan blue dye equivalent to FD&C Blue No. 1 remains an industry-wide challenge and the subject of several research programs worldwide. Computational simulations and large-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 68 publications
(75 reference statements)
3
39
0
Order By: Relevance
“…Hence, it can be proposed that C7-OH in the complexes was not dissociated at pH 6, and lost its proton when the pH is raised to 8 ( Scheme 2 ). This proposal is consistent with the theoretical visible spectrum calculated on the Al(PB) 3 complex, which, while involving 3 ligands undissociated at C7-OH, were found fully consistent with the experimental spectrum [ 8 ]. Moreover, comparing the neutral base of the 7-O-β-D-glucosyloxy-4′-hydroxyflavylium ion (proton loss from C4′-OH) with that of its 4′-O-β-D-glucosyloxy-7-hydroxyflavylium regioisomer (proton loss from C7-OH) also showed that the former displayed a λ max value that was 20 nm higher [ 14 ] and a molar absorption coefficient almost 3 times as large.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Hence, it can be proposed that C7-OH in the complexes was not dissociated at pH 6, and lost its proton when the pH is raised to 8 ( Scheme 2 ). This proposal is consistent with the theoretical visible spectrum calculated on the Al(PB) 3 complex, which, while involving 3 ligands undissociated at C7-OH, were found fully consistent with the experimental spectrum [ 8 ]. Moreover, comparing the neutral base of the 7-O-β-D-glucosyloxy-4′-hydroxyflavylium ion (proton loss from C4′-OH) with that of its 4′-O-β-D-glucosyloxy-7-hydroxyflavylium regioisomer (proton loss from C7-OH) also showed that the former displayed a λ max value that was 20 nm higher [ 14 ] and a molar absorption coefficient almost 3 times as large.…”
Section: Resultssupporting
confidence: 90%
“…The flexible acyl residue of P4′ is probably much less apt to develop π-stacking interactions with the cyanidin nucleus than the more rigid sinapoyl residue of PB. Consistently, it has been demonstrated that RC anthocyanins having a single HCA residue at R 1 (P1–P3) are much more susceptible to water addition than PB [ 8 ] as a consequence of the latter adopting folded conformations in which the cyanidin and HCA moieties are in molecular contact. However, PSP pigments have a specific advantage over RC pigments: the presence of caffeoyl residues at Glc-1 and/or Glc-2, which themselves can bind metal ions.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations